Policy Debate | Humanitarian Protection in the Midst of Civil War: Lessons from Sri Lanka - Norah Niland; John Holmes; Miriam Bradley (Revue Internationale de Politique de Développement)
Editor’s note: This paper is a contribution to the ‘Policy Debate’ section of International Development Policy. In this section, academics, policy-makers and practioners engage in a dialogue on global development challenges. Papers are copy-edited but not peer-reviewed. Instead, the initial thematic contribution is followed by critical comments and reactions from scholars and/or policy-makers.Authored by Norah Niland, the initial paper addresses the protection dimension of humanitarian action in the Sri Lankan Civil War. The end phase of this long-standing war and subsequent internment of survivors illustrate the limited capacity of the international relief system to adequately protect civilians. The author argues that the failure of intergovernmental crisis management and the human rights machinery was exacerbated by the relief system’s lack of agency in safeguarding humanitarian space and the protected status of civilians. According to Norah Niland, relief actors largely ignored the instrumentalisation of humanitarianism and the use of sovereignty and Global War on Terror (GWOT) narratives to rationalise the slaughter of thousands. The lack of accountability for and reflection on the humanitarian  operation  in Sri Lanka will likely complicate future relief efforts and add to the suffering of  civilians in other crisis settings. The paper  is followed by critical comments by Sir John Holmes, Former UN Under-Secretary General and Emergency Relief Coordinator, Head of the UN Office for the Coordination of Humanitarian Affairs, and Miriam Bradley, Postdoctoral Researcher, Programme for the Study of International Governance, the Graduate Institute, Geneva.This debate can be pursued on the eJournal’s blog http://devpol.hypotheses.org/69Download the full debate in .pdf